Gerald Finzi’s Violin Concerto: A Performer’s Perspective - Lees, William (Royal Irish Academy of Music, 2020)
While many of the choral works by Gerald Finzi have become standard repertoire, his early Violin Concerto remains relatively unknown to most, receiving only one full performance in the composer’s lifetime and lying discarded for the larger part of the twentieth century. Finzi rejected the first movement and wrote a replacement work in its stead, which in turn was also rejected along with the third movement. The original first movement has never been performed. In 1999 the Finzi Trust elected to reassemble the concerto for the composer’s forthcoming centenary and a new edition of the work was commissioned. A dissertation by Iain Cooper and books by Diana McVeagh and Stephen Banfield acknowledge the important role the Violin Concerto played in Finzi’s development as a composer. This thesis expands on these studies and revives the original discarded first movement, which has to date had little or no expression of interest. The chronology of the concerto and Finzi’s treatment of each movement are catalogued and discussed. Finzi’s Violin Concerto owes much to the models by Ralph Vaughan Williams, Gustav Holst and Ernest Bloch. These three influences are considered and analysed as are the importance of folksong, J. S. Bach and neoclassicism to the work. Through analysis of Finzi’s Violin Concerto his compositional techniques are explored and Finzi’s changes of approach in the concerto are examined and discussed. New editions of the solo violin part of all four movements, with contemporary bowings and phrasing, are discussed, which in turn further expose Finzi’s choices and influences. A performer’s approach is outlined with the difficulties in execution considered and the style explored to gain a greater understanding of this work. The original first movement, which illustrates the potential that Finzi was displaying and the flaws that kept the work from ever being performed, has been transcribed from the manuscript into digital format for ease of analysis and consideration. Ideas that Finzi had for developing the discarded movements as a clarinet concertino and the subsequent connection between Finzi’s later Clarinet Concerto is presented. Consequently the merits of reviving Finzi’s Violin Concerto, about which the composer obviously had grave misgivings, are considered.
Keywords: Music; Violin concerto; Gerald Finzi; Finzi, Gerald, 1901-1956; Concertos (Violin); Composers - England - 20th century